Answer:
![c_1e^(3x)+c_2e^(-x)+(1)/(2) xe^(3x)](https://img.qammunity.org/2021/formulas/mathematics/college/j1ihjg21ndvl4s7ba4pdtbdo21vqzwv8xb.png)
Explanation:
For homogeneous solution:
![y''-2y'-3=0\\r^2-2r-3=0\\(r-3)(r+1)=0](https://img.qammunity.org/2021/formulas/mathematics/college/32zt9vthpb53j17fw3fn5w1d7i1184ia2c.png)
So since roots are r = 3 and r = -1,
![y_h=c_1e^(3x)+c_2e^(-x)](https://img.qammunity.org/2021/formulas/mathematics/college/ec0ggu6ck8eehvo9z2936l487swuu526fj.png)
Since we are given
, we will use undetermined coefficients. However, here the trick is we have
in homogeneous solution. So in particular solution, as undetermined coefficients, we will use
instead of
.
Hence,
![Y = Axe^(3x)\\Y' = Ae^(3x) + 3Axe^(3x)\\Y'' = 3Ae^(3x) + 3Ae^(3x) + 9Axe^(3x) = 6Ae^(3x) + 9Axe^(3x)](https://img.qammunity.org/2021/formulas/mathematics/college/b3ydu91rgmp1lpia1e6j2bmkhaxqqysrpe.png)
So,
![6Ae^(3x)+9Axe^(3x)-2Ae^(3x)-6Axe^(3x)-3Axe^(3x)=2e^(3x)\\4Ae^(3x)=2e^(3x)\\A=(1)/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/jy4vh5vlqxini6blxnxrynfkihlw38ucpx.png)
Hence,
![y_p = (1)/(2) xe^(3x)](https://img.qammunity.org/2021/formulas/mathematics/college/cjw827f1wbwg7427swzi0rlobdv7nx9t37.png)
General solution is:
![y=y_h+y_p=c_1e^(3x)+c_2e^(-x)+(1)/(2) xe^(3x)](https://img.qammunity.org/2021/formulas/mathematics/college/s2yh79grc7xzodxm1s4smu71exft77u3md.png)